Including scalable nutrition interventions in a graduation model program: Experimental evidence from Ethiopia - Alderman, Harold; Gilligan, Daniel O.; Leight, Jessica; Mamo, Tigist; Mulford, Michael; Tambet, Heleene (International Food Policy Research Institute, 2023)
We explore the impact of different models of scalable nutrition services embedded within a light-touch graduation program, implemented at scale in Ethiopia. The graduation program provided poor households enrolled in Ethiopia’s national safety net, the Protective Safety Net Program (PSNP), with additional livelihood programming including savings groups, business skills training and linkages to financial services. In addition, extremely poor households received a one-time livelihood grant on an experimental basis, as cash transfers or in-kind poultry grants, at a value much smaller than lump sum transfers in other graduation model programs in recent literature. The experiment compared a core nutrition model of nutrition information and sanitation and hygiene activities to an enhanced model that added more intensive nutrition messaging, supplementary feeding of malnourished children, mental health services, and a male engagement activity. Results show that interaction with health care workers and participation in community health activities increased significantly under the enhanced nutrition model, as did maternal nutritional knowledge. Nevertheless, neither nutrition model led to significant improvements in child dietary diversity or anthropometric outcomes on average. However, cash livelihood grants combined with the enhanced nutrition model reduced childhood stunting.